Stock of biomass and nutrient in a stand of hybrid Eucalyptus urophylla x Eucalyptus grandis in Pampa Biome - RS - Carvalho, Renata Reis de; Guimarães, Claudiney do Couto; Silva, Júlio Cesar Medeiros da; Momolli, Dione Richer (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
This study aimed to estimate the stock of biomass and nutrients in a hybrid stand of Eucalyptus urophylla x Eucalyptus grandis, with 4.5 years old. In order to estimate the biomass, four plots with dimensions of 21.0 m x 27.5 m were randomly allocated. From the diameter distribution of the stand were determined four diameter classes and in each class were sampled three trees (lower, middle and top limits). To estimate the roots biomass, the collection was held in the useful area of the trees of the central limit of each class. After sampling and identification of each biomass component, they were sent to the laboratory where they were dried, weighed, ground and carried the chemical analysis. The estimated total biomass was 75 Mg ha-1 with the following proportions: wood (61.2%), root (15.4%), branches (10.2%), bark (7.7%) and leaves (5.5%). The biomass is predominantly allocated to the stem (68.9%). On average, the accumulation of nutrients was higher in the wood, followed by the leaves, roots, branches and bark. The accumulation of nutrients presented the following scale: Ca > K > N > Mg > S > P, with the higher amount of Ca allocated to the stem. The stock of nutrients in the biomass was high in relation to the low fertility soil.